Corporate Social Responsibility Disclosure: A Determinant Analysis (Case Study Manufacturing Companies Listed on the Indonesia Stock Exchange) - Meilaty Finthariasari; Erwin Febriansyah; Katra Pramadeka (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2020)
This study aims to determine the effect of environmental performance, audit committee, profitability, Leverage, and company size to corporate social responsibility (CSR) disclosure in companies listed on the Indonesia Stock Exchange. Corporate Social Responsibility disclosure measured by CSR index based on the Global Reporting Initiative (GRI) G4. The population of this study are manufacturing company listed on Indonesian Stock Exchange in 2017-2019. Data collected by documentation method and literature study. Sampling using purposive sampling method, and obtained 18 companies in each period. Sources of data obtained from annual reports of companies listed on Indonesia Stock Exchange in 2017-2019. The analytical method for this study uses multiple regression analysis with SPSS 16. The result of this study showed that environmental performance and company size has positive effect to CSR disclosure. Audit committee and profitability has not effect to CSR disclosure, while Leverage has negative effect to CSR disclosure.